Molecular identification and subtyping of Cryptosporidium spp. in laboratory mice and rats - Zhou Shanshan; Hu Xinyu; Li He; Yuan Zhongying; Li Zhen; Liu Aiqin; Jiang Yanyan; Cao Jianping (Parasite)
Cryptosporidium species can infect humans and more than 260 animal species, including 54 rodent species. However, data on the occurrence and genetic characterizations of Cryptosporidium spp. in laboratory rodents are limited. The present study aimed to determine the occurrence rate and genetic characterizations of Cryptosporidium spp. in laboratory mice and rats. We collected 506 fresh combined fecal pellet specimens (457 from mice and 49 from rats) of more than 2,000 laboratory rodents in Heilongjiang Province and Shanghai City, China. Cryptosporidium spp. were identified and subtyped by DNA sequencing of the SSU rRNA and the gp60 genes, respectively. By sequence analysis of the SSU rRNA gene, the occurrence rate of Cryptosporidium spp. was 16.6% (84/506) in combined fecal specimens, with 18.2% (83/457) for mice and 2.0% (1/49) for rats. Cryptosporidium parvum (n = 39), C. tyzzeri (n = 33), and C. parvum + C. tyzzeri (n = 11) were identified in mice. Cryptosporidium parvum was only detected in one rat fecal specimen. At the gp60 locus, 71.4% (60/84) of the Cryptosporidium-positive specimens were successfully amplified, and they all came from mice. We identified five C. parvum subtypes (IIaA14G2R1, IIaA16G2R1, IIaA17G1R1, IIaA17G2R1, and IIaA18G2R1) and two C. tyzzeri subtypes (IXaA6R1 and IXbA8). Based on the identification in laboratory mice of C. parvum subtypes that have been reported previously in humans, the mice infected with this species may threaten human health, especially for people who have contact with the animals and their feces.